2022
DOI: 10.1002/fes3.378
|View full text |Cite
|
Sign up to set email alerts
|

Starch morphological, structural, pasting, and thermal properties of waxy maize under different heat stress durations at grain formation stage

Abstract: Heat stress (HS) is a major environmental constraint in sustaining global waxy maize production under future climate condition. Starch physicochemical properties under 5‐day (HS5) and 10‐day (HS10) postsilking HS were investigated using two waxy maize hybrids (Suyunuo5 and Yunuo7) as materials. Ambient and high temperatures were 28°C/20℃ and 35°C/27℃, respectively. Starch granules were enlarged and exhibited additional pitting or cellular structures, increased amylopectin chain length, increased relative cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Each treatment included 50 pots. The soil properties in this study were the same as that previously reported [ 7 ]. In this experiment, seedlings were raised in a seeding tray and then transplanted into a pot.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Each treatment included 50 pots. The soil properties in this study were the same as that previously reported [ 7 ]. In this experiment, seedlings were raised in a seeding tray and then transplanted into a pot.…”
Section: Methodsmentioning
confidence: 83%
“…Heat stress during grain filling affects the source and sink of maize, resulting in low and unstable grain yield and quality [ 7 , 8 ]. Source capacity is directly affected by the decline in carbohydrate synthesis caused by a decrease in photosynthesis and an increase in respiration rate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Waxy maize is a special crop, characterized by a unique structure of starch, which creates enormous possibilities for its application [ 1 ]. Among the various types, waxy maize starch is distinct, with starch composed of nearly pure amylopectin, which provides advantages of viscosity, stability, and retrogradation [ 2 ]. Waxy maize was originally used mainly for industrial production, and only to a small extent for food production [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%